Bacteriological profile of patients with infective endocarditis - Kandel, NP; Banyat, SR; Koirala, B; KC, MB; Shrestha, S (Journal of Institute of Medicine Nepal, 2007)
Introduction: The term infective endocarditis (IE) denotes infection of the endothelial surface of the heart and implies the physical presence of microorganisms in lesions. Although the heart valves are commonly affected the disease may also occur within the septal defects or in the mural endocarditis1 .IE is uncommon disease but it is fatal in untreated cases. This study was carried out in Shahid Gangalal National Heart Centre (SGNHC), Bansbari, Kathmandu during 30 October 2003 to 30 June 2004 among 34 patients diagnosed as definite cases of IE. Materials and Methods: Blood culture for bacteria & antibiotic sensitivity tests were performed for each patient using standard microbiological protocol in Laboratory of SANHC. Echocardiography was done for each patient to confirm the case of IE. Questionnaires were fulfilled to get additional informations regarding the patients. Results: We found positive blood culture in 14 (41.12%) out of 34. The frequency of isolated organisms were Viridans streptococci in 6 (42.85%) cases, Staphylococcus aureus in 3 (21.43%) cases, Pseudomonas aeruginosa in 2 (14.28%) case and Coagulase negative and Staphylococci (CONS) in 3 (24.41%) cases among positive blood culture. All Gram positive bacteria were susceptible penicillin, gentamicin, cephotaxime, ceftriaxone, vancomycin and ciprofloxacin. Only less than 50% of Gram positive bacteria were susceptible to Amoxicillin, Ampicillin, Erythromycin and Cotrimoxazole. All Gram negative bacteria were susceptible to Ciprofloxacin, Tetracycline, Cotrimoxazole and Cephotaxime. Only 50% of Gram negative bacteria were susceptible to Gentamicin. Ampicillin and Amoxicillin were found to be resistant with all Gram negative bacteria. Echocardiography records revealed vegetation in 27 (79.42%) cases of whom blood culture was positive in 12 (44.44%). Conclusion: Blood culture and echocardiography are very useful for diagnosis and treatment of cases of IE. Keywords: Infective endocarditis, echocardiography, antibiotic susceptibility test. The full text of this paper is available at Journal of Institute of Medicine website